A history of Saudi Arabia - Al-Rasheed, Madawi 1962- (Cambridge University Press, 2012)
This updated edition analyses the challenges, both internal and external, facing Saudi Arabia in the twenty-first century. Two new chapters discuss the political, economic and social developments in the aftermath of 9/11, painting a vivid picture of a country shocked by terrorism and condemned by the international community. Madawi Al-Rasheed reveals that fragmentation of royal politics, a failing economy and fermenting Islamist dissent posed serious threats to state and society in 2001. She assesses the consequent state reforms introduced under pressure of terrorism, international scrutiny and a social mobilisation of men, women and minorities struggling to shape their future against a background of repression and authoritarian rule. While Saudi Arabia is still far from establishing a fourth state, there are signs that the people are ready for a serious change that will lead them to a state of institutions rather than princes
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Ibn-Saud -- Dynastie : 1932-; Geschichte 1900-2000; Geschichte 1744-1902; Geschichte; Saudi Arabia / History / 20th century; Saudi Arabia / History / 21st century; Saudi-Arabien